2012
DOI: 10.1016/j.bbamem.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the role of phosphatidylserine in modifying the susceptibility of human lymphocytes to secretory phospholipase A2 using cells deficient in the expression of scramblase

Abstract: Summary Normal human lymphocytes resisted the hydrolytic action of secretory phospholipase A2 but became susceptible to the enzyme following treatment with a calcium ionophore, ionomycin. To test the hypothesis that this susceptibility requires exposure of the anionic lipid phosphatidylserine on the external face of the cell membrane, experiments were repeated with a human Burkitt’s lymphoma cell line (Raji cells). In contrast to normal lymphocytes or S49 mouse lymphoma cells, most of the Raji cells (83%) did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Nelson et al (2011) found that A. piscivorus piscivorus PLA 2 showed different activity on hydrolyzing the membrane of ionomycin-, dexamethasone-or thapsigargin-treated cells. Although ionomycin similarly induced PS externalization of normal lymphocytes, Raji human Burkitt's lymphoma cells and S49 mouse lymphoma cells, A. piscivorus piscivorus PLA 2 differently hydrolyzed the membrane of ionomycin-treated lymphocytes, Raji cells and S49 cells (Nelson et al, 2012) Collectively, these findings suggest the notion that membrane compositions and/or membrane-bound conformation of PLA 2 enzymes should be important for the susceptibility of apoptotic cells for PLA 2 . Compared with PS-containing PC/SM/Chol and PE/Chol vesicles, PC/SM/Chol and PE/Chol vesicles show a higher membrane fluidity.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Nelson et al (2011) found that A. piscivorus piscivorus PLA 2 showed different activity on hydrolyzing the membrane of ionomycin-, dexamethasone-or thapsigargin-treated cells. Although ionomycin similarly induced PS externalization of normal lymphocytes, Raji human Burkitt's lymphoma cells and S49 mouse lymphoma cells, A. piscivorus piscivorus PLA 2 differently hydrolyzed the membrane of ionomycin-treated lymphocytes, Raji cells and S49 cells (Nelson et al, 2012) Collectively, these findings suggest the notion that membrane compositions and/or membrane-bound conformation of PLA 2 enzymes should be important for the susceptibility of apoptotic cells for PLA 2 . Compared with PS-containing PC/SM/Chol and PE/Chol vesicles, PC/SM/Chol and PE/Chol vesicles show a higher membrane fluidity.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies suggested that membrane structure contributed to the level of membrane susceptibility to A. piscivorus piscivorus PLA 2 in addition to PS externalization (Bailey et al, 2007(Bailey et al, , 2009Nelson et al, 2011Nelson et al, , 2012. Nevertheless, the effect of membrane-interacted mode of PLA 2 enzymes and membrane compositions on PLA 2 activity does not explore in the studies of Bailey et al (2007Bailey et al ( , 2009 and Nelson et al (2011and Nelson et al ( , 2012. Nelson et al (2011) found that A. piscivorus piscivorus PLA 2 showed different activity on hydrolyzing the membrane of ionomycin-, dexamethasone-or thapsigargin-treated cells.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations